(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
The computer vision syndrome has become a burning issue in this modern world with the advancement of the technology and its wide use. This study was planned to determine the prevalence of computer vision syndrome among professional computer workers as well as it’s associated risk factors. The cross-sectional study was conducted in the Departments of Community Ophthalmology and Ophthalmology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from September 2017 to February 2020. The professionals using computer on an average 4 hours per day for a duration of at least 1 year attending out patient department for having treatment for their ocular problems were the study population. A total of 77 such subjects were consecutively included in the study. In this present study, the preva- lence of computer vision syndrome (CVS) was 46.8%. The present study demonstrated that middle class and upper-middle class professionals were more likely to be associated with CVS than the lower-middle class computer professionals with risk of developing CVS in former cohort was observed to be almost 3-fold (95% CI=1.1–7.5) higher than that in the latter cohort (p = 0.027). The duration of working on computer predisposes the development of CVS with mean duration of working was on an average 1.2 years higher in subjects with CVS than that in subjects without CVS. Subjects who maintained their level of personal computer(PC) at or above their eye level (while working on computer) were more prone to develop CVS with odds of developing the condition in them being 3.6(95% CI = 1.3-9.7) times higher than the subjects who maintained the level of PC below their eye level (p = 0.010). Glare display also emerged as significant predictor of CVS with odds having the condition being 9.8(95% CI = 1.1-88.6) times higher than that with PCs without glare display (p = 0.016). Seating posture at computer also have its impact on the development of CVS. Computer workers with inappro- priate seating posture are more often associated with the development CVS. The study concluded that over one-quarter of the computer professionals suffer from computer vision syndrome (CVS). The predominant symptoms of CVS are eye strain, irritation of eye, blurred vision and headache. The factors that contribute to the development of CVS are middle class and upper-middle class professionals, prolonged working exposure to computer, level of PC at or above the eye level of the workers, glare display on the screen and inappropriate seating posture. BSMMU J 2021; 14(3): 31-37